2019
DOI: 10.3390/app9214717
|View full text |Cite
|
Sign up to set email alerts
|

Phase Noise Cancellation in Coherent Communication Systems Using a Radio Frequency Pilot Tone

Abstract: Long-haul optical fiber communication employing digital signal processing (DSP)-based dispersion compensation can be distorted by the phenomenon of equalization-enhanced phase noise (EEPN), due to the reciprocities between the dispersion compensation unit and the local oscillator (LO) laser phase noise (LPN). The impact of EEPN scales increases with the increase of the fiber dispersion, laser linewidths, symbol rates, signal bandwidths, and the order of modulation formats. In this work, the phase noise cancell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…• Phase Noise Cancellation in Coherent Communication Systems Using a Radio Frequency Pilot Tone [3] In long-haul optical fiber communication, DSP-based (digital signal processing) dispersion compensation can be distorted by the equalization-enhanced phase noise (EEPN), due to the reciprocities between the dispersion compensation unit and the local oscillator (LO) laser phase noise (LPN). In this invited paper, the authors demonstrated a unique approach for phase noise cancellation using a radio frequency pilot tone.…”
Section: Special Issue Papersmentioning
confidence: 99%
“…• Phase Noise Cancellation in Coherent Communication Systems Using a Radio Frequency Pilot Tone [3] In long-haul optical fiber communication, DSP-based (digital signal processing) dispersion compensation can be distorted by the equalization-enhanced phase noise (EEPN), due to the reciprocities between the dispersion compensation unit and the local oscillator (LO) laser phase noise (LPN). In this invited paper, the authors demonstrated a unique approach for phase noise cancellation using a radio frequency pilot tone.…”
Section: Special Issue Papersmentioning
confidence: 99%
“…The data show that this algorithm can be applied to QPSK, 16APSK and higher order communication systems. Moreover, the authors of [13] explore the impact of EEPN scale increases with the increase in the fiber dispersion, laser linewidths, symbol rates, signal bandwidths and the order of modulation formats. A 28-Gsym/s QPSK optical transmission system with a significant EEPN has been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this nonlinear aspect, special efforts are needed to investigate the effects of nonlinear distortion produced by RF-PAs, which include amplitude distortion, phase distortion [11], and the spread of signal constellations based on the quasi-memoryless Saleh model when passed through the additive white gaussian noise (AWGN) channel. This model was chosen because it involves the amplitude-to-amplitude (AM/AM) and amplitude-to-phase (AM/PM) conversion curves [12].…”
Section: Introductionmentioning
confidence: 99%